Integration of French Lexicons in New Caledonian Javanese - Subiyantoro Subiyantoro; Marsono Marsono; Wening Udasmoro (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
One of the peculiarities of New Caledonian is its French nuance, especially on the many French lexicons that either have integrated in the Javanese variant or are only borrowed. This study tries to answer the questions of what underlies the use of the French lexicons and how these lexicons integrated in New Caledonian Javanese. The data for this study were obtained through speech recordings as well as live interviews with a number of representative informants in New Caledonia. The data were collected through a qualitative manner in February 2013. Theories on language contacts, in particular with regards to loanwords, were implemented to analyze the data. The findings of this study indicate that the use of the French lexicons are caused by, firstly, the nonexistence of their equivalents in the recipient language (Javanese), secondly, Javanese speakers’ motivation to distinguish themselves from other speakers, and the tendency of the Javanese to find the practical and easier way in dealing with the French lexicons.